Markers of dementia-related health in primary care electronic health records. (3rd August 2021) - Campbell, Paul; Rathod-Mistry, Trishna; Marshall, Michelle; Bailey, James; Chew-Graham, Carolyn A.; Croft, Peter; Frisher, Martin; Hayward, Richard; Negi, Rashi; Singh, Swaran; Tantalo-Baker, Shula; Tarafdar, Suhail; et al.
Abstract: Objectives: Identifying routinely recorded markers of poor health in patients with dementia may help treatment decisions and evaluation of earlier outcomes in research. Our objective was to determine whether a set of credible markers of dementia-related health could be identified from primary care electronic health records (EHR). Methods: The study consisted of (i) rapid review of potential measures of dementia-related health used in EHR studies; (ii) consensus exercise to assess feasibility of identifying these markers in UK primary care EHR; (iii) development of UK EHR code lists for markers; (iv) analysis of a regional primary care EHR database to determine further potential markers; (v) consensus exercise to finalise markers and pool into higher domains; (vi) determination of 12-month prevalence of domains in EHR of 2328 patients with dementia compared to matched patients without dementia. Results: Sixty-three markers were identified and mapped to 13 domains: Care; Home Pressures; Severe Neuropsychiatric; Neuropsychiatric; Cognitive Function; Daily Functioning; Safety; Comorbidity; Symptoms; Diet/Nutrition; Imaging; Increased Multimorbidity; Change in Dementia Drug. Comorbidity was the most prevalent recorded domain in dementia (69%). Home Pressures were the least prevalent domain (1%). Ten domains had a statistically significant higher prevalence in dementia patients, one (Comorbidity) was higher in non-dementia patients, and two (Home Pressures, Diet/Nutrition) showed no association with dementia. Conclusions: EHR captures important markers of dementia-related health. Further research should assess if they indicate dementia progression. These markers could provide the basis for identifying individuals at risk of faster progression and outcome measures for use in research.